Factors affecting job satisfaction of non commissioned officers in sri lanka military academy - Romita De Silva (University of Jaffna, 2019)
Job satisfaction plays a significiant role to retain an effective employees. Satisfied employees are adherence towards their work which lead to improve their performance. The sucess of an organisation is highly depends on the performance of the employees. Military service is one of the most stressful jobs which needs to perform duty at any time and at any risk situation based on the demand. Consequently, retaining productive officers in long term is one of the main challenges faced by many military organisations. Premature retirement among Non - commissioned officers (NCOs) in Sri Lankan army (SLA) is high, although SLA invest huge money for recruitment, induction, training, career development, maintenance and retention of those officers. Therefore, its effects to the operational effectiveness in the field. The purpose of the study is to investigate the factors which affect job satisfaction and to measure the level of job satisfaction among the NCOs in Sri Lanka Military Academy (SLMA). 320 Non - Commissioned officers were selected as sample of the study. Questionnaires were distributed in Sinhala language among the selected participants. A multiple linear regression analysis was carried out to analyse the collected data. The findings of the study reveal that pay, benefits, relationship with supervisor, communication are significant, where p values are less than 0.05. And also reveal that there is a positive relationship between these factors and job satisfaction. Further, respondents were dissatisfied on pay and relationship with supervisors. Management should give more attention on the factors such as pay, benefits, relationship with supervisor, over workload, work pressure and operating procedures in order to increase job satisfaction level of NCOs which lead to reduce turnover and absenteeism.
Keywords: Job satisfaction; Military personnel; Non - commissioned officers (NCOs); Premature retirement